MENINGKATKAN KETERAMPILAN MEMBUAT KERIPIK KENTANG MELALUI METODE LATIHAN BAGI ANAK TUNAGRAHITA RINGAN - Sri Suprapti; Fatmawati Fatmawati; Tarmansyah Tarmansyah (Universitas Negeri Padang, 2013)
Children mild mental retardation can’t make potato chips properly. Therefore, to facilitate learning for children used training methods. The purpose of this study that the ability of children to make potato chips increases. This study uses classroom action research carried out in collaboration with colleagues. Data were collected through observation techniques and testing, and then analyzed qualitatively. and quantitative. The results show the method can improve the skills training make potato chips mild mental retardation in children.